Short Documentary Film Implementation at Al Ikhsan Beji Islamic Boarding School as a Media to Improve English Speaking in the Midst of the American Popular Culture Hegemony - Ade Christanty Yudha Bestari; Meilina Haris Mayekti; Dinar Faiza (Jurnal Sinestesia, 2020)
Today, the hegemony of American popular culture products is increasingly endemic throughout the world. Therefore, students who in fact live in Islamic boarding schools are expected to be able to use the popular culture, especially YouTube, positively. So that it can be useful for himself and others. This short documentary will be applied at Islamic Boarding School and the results will be published via YouTube. The purpose of this study was to apply the making of a short documentary film at Islamic boarding school as a media for English-language expression. As well as its influence on English Speaking. This research uses a qualitative approach using the method of "reception or aesthetic studies". With this method, students as audience become the main actors in making documentary film in Islamic Boarding Schools. The results of this study are that in the midst of the onslaught of American popular culture, students must actively participate in utilizing popular culture products, especially YouTube. Students can play a role and practice directly in making documentary short film in Islamic Boarding Schools. The short film was uploaded on YouTube. The direct participation of the students will certainly affect the students' speaking ability. This is influenced by the stages that involve the role of students actively and directly. An example is the process of determining themes and titles that are adapted to the activities of the students, then followed by writing and composing English dialogue. After the dialogue was arranged, students practiced speaking and expression according to the context of the dialogue in the documentary short film at Islamic Boarding School. The existence of Islamic Boarding School become more active in the digital era.